Influence of dicofol on the behaviour of the climbing perch, Anabas testudineus - Binoy, V V; Job, Nishitha; Thomas, K John (Indian Journal of Fisheries, 2011)
Behavioural toxicity of dicofol, a commonly used pesticide, on Anabas testudineus was evaluated. Pesticide treatment has little effect on the positional orientation of the fish during the initial days of exposure. However, alteration in positional orientation was evident from day five of exposure to dicofol. Significant reduction in opercular movement was observed in fishes exposed to the pesticide as compared with control fish. Dicofol treated fish exhibited a declining trend in food intake and foraging behaviour. The ability for sustained swimming in constantly flowing water current declined drastically